Ectopic Pregnancy: Incidence Associated with Fertility Treatment - Karla D. Jiménez-Oliver; Mario I. Ortiz; Guillermo Barragán-Ramírez (Clinical and Experimental Obstetrics & Gynecology, 2023)
Objective: To identify the impact caused by the use of assisted reproduction treatments such as in vitro fertilization (IVF), artificial insemination and ovulation-inducing drugs on the incidence of ectopic pregnancy, defined as the implantation of a fertilized ovum in a place other than the endometrium in the uterine cavity, the fallopian tube being the most frequent location. Ectopic pregnancy is considered a serious health problem for the female population of reproductive age, since it hinders fertility and increases the risk of maternal death, the main complication being hypovolemic shock associated with rupture of the ectopic gestation. Mechanism: The databases Scopus, PubMed, Web of Science and Google Scholar were searched for published studies on the incidence of ectopic pregnancy related to the use of fertility treatments. The following keywords were used: “Reproductive techniques”, “Ectopic pregnancy”, “Risk factors”, and “Infertility”. Findings in Brief: The incidence of ectopic gestations increased from 2.1% to 9.4% of pregnancies following assisted reproductive techniques. Drugs related to ovarian stimulation have been reported to increase the risk of ectopic pregnancy by up to 7.9% for clomiphene citrate and gonadotropins and 6% for aromatase inhibitors (letrozole). The use of in vitro fertilization brought an increased risk of up to 9.3 times, to a rate of 9.4% in the case of the use of intracytoplasmic sperm injection and 8.6% for embryo transfer, compared to the rates reported in natural pregnancies (1.9%). Conclusion: Surveillance, follow-up and identification of risk factors associated with assisted reproductive technologies (ART) by medical professionals are essential to timely detect ectopic pregnancy, avoid serious complications, or otherwise identify the best ART to provide patients with the lowest risk of ectopic gestations, as ART remains a valuable option for many couples who wish to conceive.